Design of Differentiated Mathematics Learning Activities on Arithmetic Sequence and Series to Support Student’s Computational Thinking Abilities - Fitri Rahmadhani; Budi Mulyono; Hapizah Hapizah (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2025)
The projected result of this research is to design valid and practical differentiated mathematics learning activities on arithmetic sequences and series to support computational thinking abilities. These activities were designed utilizing the ADDIE development model, which provides a structured framework for designing, testing, and refining learning tools. This study resulted in a validity score of 90.14% for student worksheets, 92.85% for test questions and 77.4% for practicality. The pretest average was 50.54 with a standard deviation of 18.04, while the posttest average increased to 95.92 with a standard deviation of only 3.57, indicating an increase in student consistency and performance. The findings of the N-Gain analysis conveyed that the learning method incorporating differentiated activities was considered highly effective. Overall, the implementation of the computational thinking-based differentiation learning model has also proven to be very beneficial. Based on the test results, there was a notable increase in scores on each component of computational thinking skills. The findings regarding the validity and practicality of the student worksheet (LKPD) also achieved high ratings, indicating that this learning tool is both effective and practical to use in the learning process. Implication the research differentiated learning not only improves students’ understanding of mathematical concepts, but also prepares them with critical and computational thinking skills.